Synthesis and thermal properties of high-temperature phthalonitrile polymers based on 1, 3, 5-triazines. (June 2016) - Sheng, Haitong; Zhao, Fenghua; Yu, Xiaoyan; Naito, Kimiyoshi; Qu, Xiongwei; Zhang, Qingxin
Two kinds of phthalonitrile monomers based on 1, 3, 5-triazine structure have been synthesized. The chemical structures of the phthalonitrile monomers were characterized by Fourier transform infrared and nuclear magnetic resonance spectroscopies. Differential scanning calorimetric analysis revealed the curing behavior of the monomers. Thermogravimetric analysis suggested outstanding thermal stabilities of the triazine-structured phthalonitrile polymers. Thermal decomposition kinetic analysis indicated that the activation energy of the two phthalonitrile polymers is 205.6 and 152.3 kJ mol −1, respectively. Dynamic mechanical analysis showed that the storage moduli ( E ′) are 3.62 GPa and 3.66 GPa, respectively, and glass transition temperatures of both the monomers are higher than 350°C. Postcuring effects were investigated, which showed that more excellent thermal and mechanical properties were achieved with postcuring.